Absence of significant endocrine deficiencies in benign intracranial hypertension. Issue 8 (August 1981) - Reid, Alison C; Thomson, John A
Abstract : Hypothalamic-pituitary function tests have been carried out in young, obese females with both recently diagnosed and longstanding benign intracranial hypertension. No abnormalities have been found which could be implicated in the pathogenesis of the condition, nor have we been able to demonstrate any convincing evidence of long-term hypothalamic pituitary damage. The results of these investigations can be difficult to interpret and invalid conclusions may be drawn if all factors involved are not carefully considered.